ROLE OF SUB SURFACE TEMPERATURE, SALINITY AND CHLOROPHYLL TO ALBACORE TUNA ABUNDANCE IN INDIAN OCEAN - Dian Novianto; Eko Susilo (Research Center for Fisheries, 2016)
The swimming layer is one of the important factors to get maximum catches, especially on tuna longline effort. The vertical abundance of the albacore tuna was investigated based on catch data and 3-DINDESO Ocean Model data, such as sub-surface conditions of sea water potential temperature (Temp), salinity (Sal) and mass concentration of diatoms and flagellates expressed as chlorophyll (Chl) in the Eastern Indian Ocean period 2014-2015. Combining he statistical method of generalized additive model (GAM) was performed to analysis in this study. There were seven GAM models that generated with the number of ALB vertical abundance as a response variable, and Temp, Sal, and Chl as predictor variables. Sal has highly significant (P < 0.001) while Chl and Temp significant (P < 0.01) to ALB vertical abundance. Deduced from GAMs, indicated that a negative effect of Sal on the number of ALB was observed at salinity >34.52 psu. There was a positive effect of salinity on the number of ALB, which was from 34.30 to 34.47 psu and Chl showed a positive effect of this variable on the number of ALB caught occurred between 0.01 mg/m3 and 0.12 mg/m3 in the region of high confidence level where negative effect on > 0.13 mg/m3. While ALB catches abundance varied in the temperature range with the highest frequency at 24.0-24.9 °C. Sal was the most important environmental variable to the number of ALB vertically caught, followed by Chl and Temp.